Relevance of Article 27A of Law Number 1 of 2024 to Cyberbullying - Riski A. Thalib; Suwitno Yutye Imran; Muhamad Khairun Kurniawan Kadir (Yayasan Cerdas Pedia Indonesia, 2026)
The acceleration of digitalization in Indonesia has fueled a rise in cyberbullying, which threatens personal dignity and social stability. In response, Law No. 1 of 2024 introduced Article 27A into Law No. 11 of 2008 on Electronic Information and Transactions as a specific normative instrument to address such acts. This normative legal study examines the relevance, effectiveness, and challenges of Article 27A within a human rights framework. The research findings indicate that Article 27A represents a significant legislative advancement that provides a specific legal basis for prosecuting cyberbullying. However, its implementation remains hindered by ambiguous definitions, difficulties in obtaining digital evidence, and inconsistent judicial interpretations. The study concludes that Article 27A cannot stand alone as a sole instrument. Harmonized implementing regulations, enhanced competencies of law enforcement officials, and cross-sectoral digital literacy programs are required to achieve comprehensive and effective legal protection in the virtual space.